2016
DOI: 10.1186/s12870-016-0896-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of EMS-induced mutation population for amylose and resistant starch variation in bread wheat (Triticum aestivum) and identification of candidate genes responsible for amylose variation

Abstract: BackgroundStarch is a major part of cereal grain. It comprises two glucose polymer fractions, amylose (AM) and amylopectin (AP), that make up about 25 and 75 % of total starch, respectively. The ratio of the two affects processing quality and digestibility of starch-based food products. Digestibility determines nutritional quality, as high amylose starch is considered a resistant or healthy starch (RS type 2) and is highly preferred for preventive measures against obesity and related health conditions. The top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 60 publications
4
30
0
Order By: Relevance
“…Previous studies have shown the effects of null SBE and SS genes on starch composition in durum and hexaploid wheat backgrounds [6,19,20,22,23,32,35]. No full null ssiia mutants, however, have been developed in a single hexaploid wheat genotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown the effects of null SBE and SS genes on starch composition in durum and hexaploid wheat backgrounds [6,19,20,22,23,32,35]. No full null ssiia mutants, however, have been developed in a single hexaploid wheat genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Starch branching enzymes (SBEs) and debranching enzymes (DBEs) work together to create the α-(1,6) branching patterns that are characteristic of amylopectin [8,16]. Mutations in SBE genes in cereals, including durum (genome AABB) and bread wheat (genome AABBDD), have shown an increase in amylose [6,19,20]. Starch synthase enzymes (SS) are responsible for the short chains of glucose polymers between branched clusters, thus are important for the organization of the higher structure of starch granules [8,16,21].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown the effects of null SBE and SS genes on starch composition in durum and hexaploid wheat backgrounds [7,28,29,31,32,35,42,43]. Yamamori et al (2000) developed a full null ssiia individual by crossing three different wheat varieties that contained null ssiia in each subgenome [31].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a modest population size (3,634 M 1 ) was assessed to obtain mutations in most genes of the wheat genome. In previous reports, varying population sizes (from 1,536 to 6,066) were used for identifying mutations in hexaploid wheat genome [ 41 44 ]. Population sizes can be increased to increase the chances of retrieving multiple deleterious alleles in all genes.…”
Section: Discussionmentioning
confidence: 99%